Court Interpreting and Access to Justice for Foreign Defendants in Bali - I Wayan Ana (Glosains: Jurnal Sains Global Indonesia, 2026)
Background: Despite extensive international research on court interpreting, little empirical evidence exists regarding its practical implementation and user-centered evaluation in Indonesian courts, particularly in cases involving foreign defendants. Objective: This study evaluates the performance and challenges of court interpreters in supporting foreign defendants' access to justice in Bali. Methods: This research employs a descriptive quantitative design with complementary qualitative interpretation of findings. Data were collected through structured interviews and Likert-scale evaluations involving 16 participants (four defendants, four prosecutors, four lawyers, and four interpreters). Results: The findings show notable disparities in interpreter evaluations across stakeholder groups: defendants rated interpreter performance moderately (3.375/5), while prosecutors provided a significantly higher assessment (4.557/5). Defendants reported limited interpreter availability during early police examinations and concerns regarding neutrality, whereas interpreters identified legal terminology and rapid information processing as key challenges. Conclusion: This study contributes empirically to access-to-justice scholarship by demonstrating how stakeholder perceptions reveal structural inconsistencies in interpreter provision within Indonesian courts. Strengthening standardized certification, specialized legal training, and early-stage interpreter deployment is essential to enhance procedural fairness for foreign defendants.